Improving the Performance and High‐Field Stability of FAPbBr3 Single Crystals in X‐Ray Detection with Chenodeoxycholic Acid Additive. Issue 4 (2nd February 2023) - Jiang, Wei; Ren, Jiwei; Li, Haibin; Liu, Dan; Yang, Lijun; Xiong, Ying; Zhao, Yiying
Abstract: Organometal halide perovskite single crystals are one of the most promising radiation detection materials due to their unique advantages of high absorption coefficient, long carrier diffusion length, and low defect density. However, the severe ion migration in perovskites deteriorates the X‐ray detection performance under longtime and high‐field operating conditions. This work reports an effective additive of chenodeoxycholic acid (CDCA), which can suppress the ion migration and improve the performance and the operational stability of FAPbBr3 single crystals (SCs) in X‐ray detection significantl. The CDCA molecules in precursors effectively suppress the decomposition of FA ions, resulting in a better crystal orientation and stoichiometry. The trace amounts of CDCA residues in FAPbBr3 SCs improve the thermal stability and effectively suppress the ion migration. The resulting detector shows an impressive X‐ray sensitivity up to 21 386.88 µC Gyair −1 cm −2 under −500 V and a detection limit of 15.23 nGyair s −1 . The response current of the detector at 225 V cm −1 field is barely changed under the 7200 s irradiation with a dose rate of 1.949 mGyair s −1 . This work provides insights for the additive selection and improving the operational stability of perovskite single crystals for commercial applications. Abstract : Ion migration deteriorates the longtime and high‐field operational stability of perovskite X‐ray detectors. This work reports an effective additive of chenodeoxycholic acid for FAPbBr3 single crystals, which demonstrates an impressive sensitivity up to 21 386.88 µC Gyair −1 cm −2 under −500 V and an amazing operational stability at 225 V cm −1 with a dose rate of 1.949 mGyair s −1 .